Different responses to doxorubicin-induced chromosome aberrations in Brazilian deer species - Vargas-Munar, D. S. F. [UNESP]; Sarria-Perea, J. A. [UNESP]; Duarte, J. M. B. [UNESP] (Funpec-editora, 2010)
The tendency toward chromosome fragility is one of the theories that may explain chromosome variation in brocket deer species (genus Mazama). We tested doxorubicin as an inducer of chromosome aberrations in lymphocytes of three brocket deer species, Mazama gouazoubira, M. americana and M. nana, compared to the marsh deer, Blastocerus dichotomus. Doxorubicin, at a concentration of 0.25 mu g/mL, induced chromosome aberrations and fragile sites in all four species; the highest frequencies were seen in M. gouazoubira; they were lowest in B. dichotomus and intermediate in M. americana and M. nana. These results were expected based on previous karyotypic studies, but they failed to explain the higher sensitivity seen in M. gouazoubira. This may be because not all the aberrations and fragile sites are related to chromosome evolution in brocket deer; other factors, such as environmental influences, may be involved in chromosome fragility.
Keywords: Blastocerus; Cervidae; Chromosome evolution; Chromosome fragility; Mazama